PENGENDALIAN MUTU BIJI KOPI ROBUSTA MENGGUNAKAN NEW SEVEN QUALITY CONTROL TOOLS (STUDI KASUS PADA PTPN XII KABUPATEN JEMBER) - Yuli Wibowo; Yuniarsih Handayani, Rhoiyfah (Jurnal Penelitian Sains dan Teknologi Indonesia, 2022)
This study aims to apply the new seven quality control tools (new 7QC tools) method in controlling the quality of robusta coffee beans in state-owned plantation companies. This research is a case study at PT. Perkebunan Nusantara XII, Silosanen Plantation, Jember Regency. Data processing uses the new 7QC tools method which consists of three stages, including (i) identification of quality problems using affinity diagrams and relationship diagrams; (ii) analysis of quality problems using tree diagrams, matrix diagrams, and matrix data analysis; (iii) planning quality improvement using arrow diagrams and process decision program charts. The results showed that quality 1 of robusta coffee beans which were considered defective were recorded at 21.81%. The results of the identification of the main cause of the emergence of defects in the coffee beans are the lack of supervision during the processing. The results of the analysis of quality problems indicate that improving the supervision of workers, can be started by focusing on each worker's tasks in improving worker performance, better environmental and material conditioning, method improvement, and optimization of machine use. The recommended improvement plans to improve supervision of workers include carrying out production activities according to a predetermined sequence and determining the number of workers according to production needs to facilitate supervision.